HUBUNGAN BUDAYA ORGANISASI DENGAN KOMITMEN ORGANISASI PERAWAT BAGIAN RAWAT INAP KELAS II DAN III RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Darajat, Luthfah Nurfaizah; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2012)
Background: The Hospital of PKU Muhammadiyah Yogyakarta is a hospital that has an Islamic background. Based on the writers observation that was made on March 2, 2011 at the inpatient RS PKU Muhammadiyah Yogyakarta, in getting that there are many patients who should be treated in the inpatient section contained three classes of complexity in it, both in terms of economic and social class. This is a challenge for nurses in the hospitalization. Based on the results of interviews with staff personnel at the hospital found that PKU Muhammadiyah Yogyakarta there are regular activities for the employees of lectures every Wednesday and Saturday. For employees with years of service 15, 20, 25 and 30 years there is also a reward that is usually given on special milad hospital. This is part of organizational culture in hospitals. Based on the above, the author wants to examine the relationship of organizational culture with organizational commitment of nurse inpatient section class II and III hospital PKU Muhammadiyah Yogyakarta. Methods: This study was an analytical cross sectional study design. Hypothesis test used was kendalls tau correlation. The sampling technique used is saturated sampling. Instrument in the study is a questionnaire. Results: Based on bivariate analysis of organizational culture with the organizational commitment, obtained P value 0.008 < ? 0.05, for the analysis of bivariate sub variable the demand of work, interpersonal relations, support work and the physical work environment with a organizational commitment the obtained the P value in a row 0.016, 0.024, 0.041, 0.044 < 0.05, which means that there is a significant relationship of organizational culture and its sub-variables with organizational commitment of nurse-inpatient section class II and III hospital PKU Muhammadiyah Yogyakarta. Conclusion: There was a significant relationship of organizational culture and sub variable the demand of work, interpersonal relations, support of work and the physical work environment with organizational commitment of nurs-inpatient section class II and III hospital PKU Muhammadiyah Yogyakarta. Keywords: Organizational culture, demand of work, interpersonal relationship, support of work, the physical work environment, organizational commitment.